AGROCHEMICAL AND AGROPHYSICAL PROPERTIES OF IRRIGATED SOILS OF MIRZAOBOD DISTRICT (ON THE EXAMPLE OF YANGIOBOD LAND) - Ashirova Zilolakhan Ilhomjon kizi,Sun Jun,Musurmanova Mohinur Murot kizi (International Journal of Literature and Language Studies, 2026)
The morphological characteristics and mechanical composition of the experimental plots were studied. Detailed information on the agrochemical and agrophysical properties of the irrigated plots of the Yangiabad land is provided. The